2020
DOI: 10.1523/eneuro.0403-19.2020
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Nasal Inflammation and Odor Deprivation on Layer-Specific Degeneration of the Mouse Olfactory Bulb

Abstract: Harmful environmental agents cause nasal inflammation, and chronic nasal inflammation induces a loss of olfactory sensory neurons (OSNs) and reversible atrophy of the olfactory bulb (OB). Here, we investigated the mechanisms underlying this inflammation-induced OB atrophy by histologically and biochemically comparing the OB changes in mouse models of nasal inflammation and odor deprivation. In addition, we examined whether odor stimulation is necessary for OB recovery from atrophy. One group of adult male C57B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
45
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(52 citation statements)
references
References 45 publications
7
45
0
Order By: Relevance
“…Mice were consistently housed in groups separated by gender. The intranasal administration was performed according to our previous study [6][7][8] . Briefly, the mice were anesthetized with isoflurane and 10-µL physiologic saline (saline-treated mice) or LPS from Escherichia coli O55:B5 (1 mg/mL; Sigma) (LPS-treated mice) was administered to bilateral nostrils three times per week for 9 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…Mice were consistently housed in groups separated by gender. The intranasal administration was performed according to our previous study [6][7][8] . Briefly, the mice were anesthetized with isoflurane and 10-µL physiologic saline (saline-treated mice) or LPS from Escherichia coli O55:B5 (1 mg/mL; Sigma) (LPS-treated mice) was administered to bilateral nostrils three times per week for 9 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…administration of LPS causes dendritic retraction and axonal instability of TCs, but not MCs, in the mouse OB. The superficial OB layers (GL, ONL, sEPL) are the primary region of OB atrophy and inflammation at 10 weeks of LPS administrations 29,30 . Our results suggest that the reduction of dendrites that was observed in the ipsilateral OB is primarily attributed to a reduction in the sEPL.…”
Section: Discussionmentioning
confidence: 99%
“…For analyses of recovery, one group of eight-week-old +/Het mice (n=3) underwent unilateral 10week LPS administrations as discussed previously 23,29,30 and were subsequently housed for 10 weeks with no additional treatment. Three days prior to being sacrificed for immunohistochemical analyses, mice were intraperitoneally injected with tamoxifen (30 mg/kg).…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gray matter volume within the primary and secondary olfactory cortices was also significantly increased 3 months after surgical treatment for CRS ( Güllmar et al, 2017 ; Whitcroft et al, 2018b ). Furthermore, an animal study demonstrated that neuroplastic changes in the olfactory bulb were directly associated with nasal inflammation ( Hasegawa-Ishii et al, 2019 ) and loss of olfactory sensory neuronal activity rather than neuroinflammation in the olfactory bulb was the major cause of inflammation-induced olfactory bulb atrophy ( Hasegawa-Ishii et al, 2020 ). It can be inferred that controlled nasal inflammation by surgical procedure or medical treatment contributes to the improvement of peripheral olfactory function and subsequent recovery of the olfactory bulb volume and gray matter volume.…”
Section: Clinically Meaningful Classification Of Olfactory Dysfunctiomentioning
confidence: 99%